Wedding Customs of the Jawi Peranakan Indian-Muslim Community of Penang: (Adat Perkahwinan Masyarakat Jawi Peranakan India Muslim di Pulau Pinang) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
This research aimed to study the extent to which Hindu influences are sill present in the wedding customs of the Jawi Peranakan community in Penang. It also aimed to identify practices contrary to Islam still maintained in these wedding customs. The methodology employed in this research was a combination of library research, field work and interviews involving 20 male and female respondents from Georgetown, particularly from the vicinity of the Kapitan Keling Mosque. The findings are that the majority of the Jawi Peranakan community still practice the customs and traditions of their forebears but have blended into these local Malay customary practices, especially in their wedding ceremonies. They believe that adherence to their ancestral traditions and taboos will bring about harmonious and happy marriages. Also, it was found that the Jawi Peranakan of Penang still practice customs and traditions that are still largely influenced by Hindu tradition, with some practices even being in contravention with the requirements of Islam. It is hoped that this research will aid in the understanding of which wedding practices are in line with Islamic teachings, and which ones are not.Keywords: wedding customs, Jawi Peranakan of Penang, Hindu influence, Islamic law